Implementation of Bethesda system in thyroid aspirate: A cyto-histopathological correlation study (Journal of Pathology of Nepal, 2016)
Background: Thyroid lump is a common clinical problem in Nepal. The risk of malignancy has to be judged prior to surgery for which fine needle aspiration cytology is widely used. To bring the uniform reporting of thyroid aspirates, the Bethesda system for reporting thyroid cytopathology (TBSRTC) was introduced in 2007. This study was done to evaluate the various cytomorphological patterns of thyroid aspirate and to correlate the Bethesda system with final histopathology report.Materials and Methods: Fine needle aspiration were performed and were evaluated as per TBSRTC criteria. Fine needle aspiration cytology report were compared with biopsy specimen whenever possible.   Result: A total of 386 cases were studied. The sensitivity, specificity, positive predictive value, negative predictive value and overall accuracy of TBSRTC were 75.2%, 98.2%, 90.0%, 94.7% and 94.03% respectively. Conclusion: Use of TBSRTC in reporting thyroid cytopathology has a greater accuracy; however, benign cases need regular follow up as there are false negative cases.